Difficulties faced by non-native translators in translating figurative local Libyan language to English - Mohammed Alhemmair Alwash, Lutfi Mohammed; Abdullah, Muhammad Alif Redzuan (Human Resource Management Academic Research Society, 2022)
This study aims to explore the obstacles when translating the figurative metaphor in vernacular Libyan Arabic language to the English language that was employed in the speech of the former Libyan President Al Ghaddafi in his last speech, and difficulties of understanding the meanings hidden in his figurative language that could be faced by Arabic language translators but Libyan translators who know more about their vernaculars spoken by Libyans. The objective of the study was to identify and analyze the obstacles in meaning for a literal translation of Al Ghaddafi's speech by focusing on words, not in meaning required by the speaker by ignoring the cultural contexts, with no focus on the lexicon used. The last speech was broadcast on Libyan TV on 22\2\2011 before he was overthrown from power as a president of Libya. Nord’s (1991) model of text analysis was used as a theoretical framework to analyze the obtained data. Nord’s text analysis model consists of two main aspects: extratextual and intertextual factors. It gives a framework that allows both the source and potential target text to be analyzed. Both macro analysis (semantic macrostructures) and microanalysis (local semantics) were conducted. The results of the study revealed that this speech has its distinctive features, and that language was used delicately to arrive at the intended goals of the speaker. Furthermore, the result of the study revealed that the semantic phenomena employed has the correct effect of meaning not the literal meaning of the word, therefore, in the vernacular language of any language a strong cultural background shall be needed for any translator, and our example here in the Arabic language which has more than twenty vernaculars that are spoken by millions but in our example translating the meaning by a Moroccan or Iraqi translator will be a huge obstacle for him when translating a word by word meaning and leaving the semantic meaning of the word in the Libyan vernacular meaning that will mention as (LLL) Libyan Local Language.